2018
DOI: 10.1002/cche.10086
|View full text |Cite
|
Sign up to set email alerts
|

Milling performance of waxy wheat and wild‐type wheat using two laboratory milling methods

Abstract: Background and objectives Flour and starch from waxy wheat (Triticum aestivum L) have unique properties such as high water‐holding capacity, low pasting temperature, low syneresis, and high resistance to retrogradation. However, the milling performance of waxy wheat was not well documented. In this study, the milling quality of a waxy wheat (Mattern) was evaluated by comparing its flour yield, chemical composition, flow properties, and particle size distribution with that of two wild‐type hard red winter (HRW)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 23 publications
2
8
2
Order By: Relevance
“…The flour yield of Eldija and Sarta was much lower than Skagen, but the flour output can be improved if a specific milling process is used for waxy wheat (Xu et al 2018). Characterising the dough rheological properties can be effective for predicting the processing behaviour and for controlling the quality of the food products.…”
Section: Original Papermentioning
confidence: 99%
“…The flour yield of Eldija and Sarta was much lower than Skagen, but the flour output can be improved if a specific milling process is used for waxy wheat (Xu et al 2018). Characterising the dough rheological properties can be effective for predicting the processing behaviour and for controlling the quality of the food products.…”
Section: Original Papermentioning
confidence: 99%
“…Flour yields of the four waxy wheats were between 62% and 66% (Table 1), similar to those of waxy wheats (60.4%−67.2%) reported by Sayaslan et al (2006), but slightly lower than that of the normal wheat (67.3%, Table 1). Previous studies also reported a lower flour yield for waxy wheat when compared to normal wheat (Sayaslan et al, 2006; Xu et al, 2018). No correlation was found between flour yield and characteristic of kernel weight, test weight, or hardness index of the four waxy wheats (Table 1).…”
Section: Resultsmentioning
confidence: 84%
“…In a study by Xu et al. (2018), the researchers reported that for the same hardness, there was a higher degree of damage observed in waxy wheat than in wild wheat. This was attributed to the presence of semicrystalline and amorphous starch structures.…”
Section: Important Pulse Properties From a Milling/processing Perspec...mentioning
confidence: 97%
“…Researchers reported that harder grains require more rigorous milling conditions and lead to higher starch damage (Kwak et al, 2017;Makowska et al, 2014;Schutyser et al, 2015). In a study by Xu et al (2018), the researchers reported that for the same hardness, there was a higher degree of damage observed in waxy wheat than in wild wheat. This was attributed to the presence of semicrystalline and amorphous starch structures.…”
Section: Starch Damagementioning
confidence: 99%